2012
DOI: 10.1080/19361521.2012.719596
|View full text |Cite
|
Sign up to set email alerts
|

Coping Strategies as Mediators of the Relationship between Chronic Exposure to Missile Attacks and Stress Reactions

Abstract: The aim of this study was to investigate the role of coping strategies as mediators of the relationships between exposure and stress reactions after exposure to missile attacks. Data were gathered from 145 adolescents during several months in 2008, after seven years of ongoing missile attacks. Adolescents filled out self-reported questionnaires that included demographics, level of exposure to missile attacks, Adolescent Coping Scale, and stress reactions of state anxiety, state anger, and psychological distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…It should be noted that while the south of the country was the hardest hit by the attacks, missiles were directed towards the centre and a few also in the north. It follows that an underlying assumption of the study was that the participants were all at risk of experiencing traumatic stress (for additional studies on responses to stress during missile attacks in Israel, see Braun‐Lewensohn, Sagy, & Roth, ; Braun‐Lewensohn, ).…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that while the south of the country was the hardest hit by the attacks, missiles were directed towards the centre and a few also in the north. It follows that an underlying assumption of the study was that the participants were all at risk of experiencing traumatic stress (for additional studies on responses to stress during missile attacks in Israel, see Braun‐Lewensohn, Sagy, & Roth, ; Braun‐Lewensohn, ).…”
Section: Methodsmentioning
confidence: 99%
“…Coping strategies may yield either positive or negative results. They were found to be an important feature, which moderates the association between exposure to stress and mental health in various contexts ( 21 , 22 ). Lazarus and Folkman ( 19 ) suggested two major forms of coping: problem-focused (dealing with stress sources and taking proactive steps to change them) or emotion-focused (serving to reduce the emotional stress resulting from such situations) [See also: ( 23 )].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of whether a situation represents a threat or a challenge determines the level of arousal and which of the coping resources one has in his/her repertoire that will be drawn upon to deal with the situation [15]. Studies that have examined this variable in the context of war and terror have shown that women are more vulnerable and report more feelings of danger as compared to men [16]. Research has shown that these feelings seem to be an independent predictor of a variety of mental-health symptoms.…”
Section: Introductionmentioning
confidence: 99%